Book Review : Social and Environmental Accounting - Lee C. Moerman (Australasian Accounting, Business and Finance Journal, 2010)
This edited 4 volume set comprises a selection of published papers in the field of social and environmental accounting, and is the latest series of books to emerge from the Centre for Social and Environmental Accounting Research (CSEAR) at the University of St Andrews, Scotland. The editors are: Rob Gray, Professor of Social and Environment Accounting and Director of CSEAR; Jan Bebbington, Professor of Accounting and Sustainable Development and Director of the St Andrews Sustainability Institute; and Sue Gray, Research Fellow and Administrator of CSEAR. The books trace 40 years of development of social and environmental accounting (SEA) through the reproduction of 80 key articles across the four volumes. The publication coincides with concerns and reporting challenges driven largely by the increase in size and influence of the corporate entity and global capitalism (Gray, Bebbington & Gray 2010). The editors intertwine two strands of thought: the need for corporations to expand the scope of responsibility and accountability relationships; and the consideration of sustainability in the face of environmental uncertainty.
Keywords: Social and environmental accounting; SEA; Book reviews